Pengaruh Label Halal Dan Kualitas Produk Terhadap Minat Beli Konsumen Pempek Dua Putri Pada Masyarakat Muslim Kota Jambi - Nurul Ismainy Putri; Agustina Mutia; Ogi Saputra (JOURNAL SAINS STUDENT RESEARCH, 2023)
Currently, competition in the culinary business is getting tighter every day. This is evidenced by the large number of culinary businesses, one of which is MSMEs. Pempek Dua Putri is one of the MSMEs in Jambi City. Everyone has their own choices before deciding to buy a product. Halal labeling and product quality are one of the factors that influence consumer buying interest. This study aims to determine and analyze the effect of halal labeling and product quality on consumer buying interest in Pempek Dua Putri for Muslim communities in Jambi City